The girl from Greenwich Street [large type] : a novel of Hamilton, Burr, and America's first murder trial - Willig, Lauren (William Morrow Large Print, an imprint of HarperCollinsPublishers, 2025)
Bitter rivals Hamilton and Burr unite to defend a carpenter accused of murdering Elma Sands, a mysterious young woman found in a well, intertwining a high-profile trial with their own political ambitions and personal enmity.